Computational fluid dynamics simulation of tree effects on pedestrian wind comfort in an urban area. (May 2020) - Kang, Geon; Kim, Jae-Jin; Choi, Wonsik
Highlights: A CFD model successfully reproduced the previous field measurement results. Pedestrian wind comfort was investigated both in the presence and absence of trees using the CFD model. Poor wind comfort was simulated mainly beside buildings and over unobstructed wide surfaces. Wind comfort inside the target area was overall improved by wind speed reduction due to tree drag. Abstract: In this study, we applied a computational fluid dynamics (CFD) model incorporating a tree drag parameterization scheme to investigate how the presence of trees improved pedestrian wind comfort on the urban campus of Pukyong National University (PKNU). We comprehensively analyzed pedestrian wind comfort considering wind inflow direction and observed frequency. To validate the CFD model, we conducted sensitivity simulations by varying the vertical profiles of leaf area density (LAD) and compared our CFD simulations with previous field measurements and simulation results. The adjusted LAD profile yielded the best reproduction of measured wind speeds and turbulent kinetic energy behind trees, demonstrating performance similar to that of a large-eddy simulation (LES) model. We applied the CFD model to investigate the effect of trees on pedestrian wind comfort on the PKNU campus. Trees markedly improved pedestrian wind comfort when horizontally incoming airflow passed through the trees; however, there was little improvement in pedestrian wind comfort in regions where airflow rapidly descended the walls of tall buildings.